Determinants of Full Breastfeeding at 6 Months and Any Breastfeeding at 12 and 24 Months among Women in Sydney: Findings from the HSHK Birth Cohort Study - Chimoriya, Ritesh; Scott, Jane; John, James R; Bhole, Sameer; Hayen, Andrew; Kolt, Gregory S; Arora, Amit (MDPI AG, 2020)
The aim of this study was to report on breastfeeding duration up to 24 months and determine the predictors of breastfeeding duration among women in South Western Sydney, one of the most culturally diverse and socioeconomically disadvantaged regions of New South Wales (NSW), Australia. Mother–infant dyads (n = 1035) were recruited to the Healthy Smiles Healthy Kids birth cohort study. Study data were collected through telephone interviews at 2, 4, 8, 12, and 24 months postpartum. Cox proportional hazards models were used to determine factors associated with the risk of stopping full breastfeeding at six months and any breastfeeding at 12 and 24 months. The majority of mothers (92.3%) had initiated breastfeeding. At six months, 13.5% of infants were fully breastfed, while 49.9% received some breast milk. Only 25.5% and 2.9% of infants received some breast milk at 12 and 24 months, respectively. Lower maternal education level, lower socioeconomic status, full-time employment, maternal smoking during pregnancy, and caesarean delivery were associated with increased risk of stopping full breastfeeding at six months and any breastfeeding at 12 and 24 months. Older maternal age and partner’s preference for breastfeeding were associated with an increased likelihood of continuing any breastfeeding at 12 and 24 months. These findings present a number of opportunities for prolonging breastfeeding duration in disadvantaged communities in NSW.